THE EFFECT OF IC-BASED GROUP COUNSELING (INTRA COMMUNICATION INTEGRATIVE) TO REDUCE CAREER ANXIETY OF STUDENTS OF SMA NEGERI 1 BATAUGA - Megawidya Wati Nurdin; Farida Aryani; Abdul Saman (LP2M IAI Al-Khairat Pamekasan, 2026)
The effect of ICI (Intra Communication Integrative) based group counseling on reducing career anxiety among students at SMA Negeri 1 Batauga. The method used is a quantitative approach with a quasi-experimental design, involving 20 students divided into experimental and control groups. Data were collected through observation, a career anxiety scale, and documentation. The results indicate that students' career anxiety was at a high level before the intervention. After receiving ICI-based group counseling, there was a significant reduction in the level of career anxiety among students. Statistical analysis shows that ICI-based group counseling is effective in helping students manage their career anxiety, with a shift from a high category to a moderate category. These findings emphasize the importance of an intrapersonal communication approach in counseling to enhance self-awareness and students' confidence in planning their career futures.